Preventive Activities of Forensic Vehicle Examiners - N. N. Il’in (Теория и практика судебной экспертизы, 2023)
Preventive activities of forensic vehicle examiners are growing to be more and more important. This largely depends on the expert’s level of specialized knowledge, which he applies when investigating traffic accidents and crimes. These highly topical problems are mainly related to conceptual and classification issues of vehicle examinations, the definition of their subject, objects, and tasks, as well as with the proposals in the field of methodological support.The article addresses the issues of preventive activities of forensic vehicle examiners, analyzes scientific sources, examples of investigative and judicial practice, as well as current legislation. The author presents some recommendations on improving the level of transport security and prevention of traffic accidents.